Enhancing the Oxidative Stability of Beeswax–Canola Oleogels: Effects of Ascorbic Acid and Alpha-Tocopherol on Their Physical and Chemical Properties - Sonia Millao; Marcela Quilaqueo; Ingrid Contardo; Mónica Rubilar (Gels)
The choice of antioxidant to be used in the formulation of an oleogel is crucial to determine its oxidative stability and functionality, as these factors can also affect the physical, chemical, and rheological properties of the oleogel. In this study, the effect of two antioxidants (ascorbic acid, AA, and alpha-tocopherol, AT) and their concentration (0.01, 0.02, and 0.03%) on the physical and chemical properties of beeswax and canola oil oleogels were evaluated. The results show that the type and concentration of antioxidants did not affect the thermal properties of the samples, and in FTIR analyses, no noticeable changes in spectra patterns are observed. Rheological analyses showed that the oleogels containing AA exhibited higher elasticity and resistance to deformation. Accelerated oxidative stability tests (storage at 50 °C and the Rancimat test) showed that AA effectively delayed oxidation. The induction time increased by 2.61-fold at higher concentrations, while AT did not significantly affect oxidation resistance. Overall, it was observed that AA improved oleogel firmness and OBC (up to 1.75-fold and 2.8%, respectively), whereas AT resulted in a softer and less stable gel structure. These results show the importance of antioxidant selection, indicating that hydrophilic antioxidants have promising applications in the formulation of beeswax oleogels.